A bio-based N-heterocyclic poly(aryl ether ketone) with a high biomass content and superior properties prepared from two derivatives of guaiacol and 2, 5-furandicarboxylic acid. (January 2022) - Zhang, Rui; Bao, Feng; Weng, Zhi-Huan; Zong, Li-Shuai; Wang, Jin-Yan; Jian, Xi-Gao
Highlights: Novel bio-based poly (aryl ether ketone) from FDCA and guaiacal with the highest biomass content. The optimum conditions for the reaction using orthogonal experiments. Excellent thermal properties, mechanical properties, thermoforming solution processablity. Study of mechanism of polymerization by analyzing the molecular simulations and the properties of the resins. Abstract: To reduce the dependence on non-renewable resources and to address environmental issues, bio-based high-performance poly(aryl ether ketone), PGFEKK, is prepared using two bio-based monomers derived from guaiacol and 2, 5-furandicarboxylic acid. With a biomass content of 64.9%, it is the highest biomass content for poly(aryl ether ketone)s reported to date. In this report, the reaction of the bio-based monomers 6-(4-hydroxy-3-methoxyphenyl) pyridazin-3(2H)-one (GSPZ) and furan-2, 5-diylbis((4-fluorophenyl)methanone) (BFBF) is carried out via base-catalyzed nucleophilic substitution. The optimum conditions for the reaction are studied using orthogonal experiments and PGFEKK is obtained with a molecular weight up to 21.5 kg/mol, a glass transition temperature of 212 °C, a 10% weight loss temperature of 452 °C, and a tensile strength of 84 MPa. In addition, PGFEKK has a melt viscosity of only 207 MPa at 329 °C and dissolves in most solvents at room temperature. Such a high-performance bio-based poly(aryl ether ketone) has never been reported before. Furthermore, to study the mechanism of how two bio-based monomers affected the polymerization process and material properties, three other polymers are prepared using two petroleum-based monomers, DHPZ and BFBB, instead of GSPZ and BFBF, by analyzing the molecular simulations and the properties of the materials.